Improved oxidation resistance of a nanocrystalline lanthanum-implanted FeCr alloy - S. Khaerudini, Deni; Othman, M. A.; Mahzan, S.; Untoro, P.; Sebayang, D. (Elsevier, 2011)
The decrease in the solid oxide fuel cell (SOFC) operating temperatures from 1000 to 850 ºC has enabled the use of ferritic alloys, especially FeCr alloy, as interconnects instead of ceramics. However, there are many problems remaining such as the chromia scale growth and chromium evaporation into cells that can cause degradation in the SOFC performance. Therefore, in the SOFC using metallic interconnects the stability of the alloy at the operation temperature is the greatest technical challenge. In this study, the causes of the difference to the oxide scale growth rate was investigate by focusing on the oxide scale, and improve the more protective surface treatment in order to reduce further not only the oxide scale growth but Cr evaporation. The effectiveness of the nanostructure and surface treatment in improving the oxidation resistance of the alloy was demonstrated by oxidation tests at 900 °C in air corresponding to the cathode environment of SOFC. The surface and cross-sectional morphologies of the alloy after thermal exposure were evaluated and observed using scanning electron microscopy with an energy dispersive X-ray spectroscopy. The phase structures of oxide scale formed on them were identified by X-ray diffraction.